Migration to study in medical schools of Peru - Chambergo-Michilot, Diego (2020)
The aim of this study was to describe the frequency of migration to study medicine in Peru. We conducted a secondary data analysis of the Red-LIRHUS study (2011-2012). We included 3 680 Peruvian students. Approximately, 23.2% migrated for medical school. Less than 1% were international migrants. We found a higher proportion of migrant students in Universities outside of Lima than in Universities in Lima (27.1% vs. 15.8%). There was also a higher proportion of migrants in private universities (28.3% vs. 16.0%) Migrant students were more likely to live alone (27.4% vs. 6.4%) and to report having failed a module/course (51.0% vs. 38.6%) compared to non-migrant students. It is necessary to evaluate potential interventions for the preservation of the well-being of people who migrate for their medical training.